2004
DOI: 10.5713/ajas.2004.1271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feeding Processed Soy Protein on the Growth Performance and Apparent Ileal Digestibility in Weanling Pigs

Abstract: For Exp. 1, one hundred twenty Duroc×Yorkshire×Landrace pigs (6.34±0.70 kg average initial BW) were used in a 35 d growth assay. There were six pigs per pen and four pens per treatment. Dietary treatments included 1) NC (negative control; basal diet), 2) PC (positive control; added 5% HP 300  , HAMLET PROTEIN A/S, as protein source), 3) PSP 2.5 (added 2.5% Pepsoygen  , Genebiotech Co. Ltd., as protein source), 4) PSP 5.0 (added 5% Pepsoygen  as protein source), and 5) PSP 7.5 (added 7.5% Pepsoygen  as prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 24 publications
5
36
1
Order By: Relevance
“…A linear increase in ADFI because of feeding processed soya proteins was also reported by Min et al (2004). The findings in the present study once again confirmed that FSP could significantly improve the ADG than SBM fed group that we reported earlier (Yun et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…A linear increase in ADFI because of feeding processed soya proteins was also reported by Min et al (2004). The findings in the present study once again confirmed that FSP could significantly improve the ADG than SBM fed group that we reported earlier (Yun et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…The lower apparent digestibility of nutrients lowered the ADG in this group. Higher DM and N digestibilities were also reported in pigs fed processed soya protein diet than to negative control (without processed soya protein) by Min et al (2004). As previously discussed, the FSP contained smaller peptides that could be easily digested by digestive proteases and this could be the reason that the CP digestibility was improved in FSP fed pigs.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations